PENDIDIKAN ANTI KORUPSI DI SEKOLAH DASAR DALAM PERSPEKTIF FILSAFAT PENDIDIKAN - Heny Puspita Sari; Muhammad Nurwahidin; Sudjarwo, Sudjarwo (Journal of Innovation Research and Knowledge, 2022)
Anti-corruption education is very appropriate to be implemented at the elementary school level, where the conformity of anti-corruption education's aspects, values, and principles demonstrates the relevance of anti-corruption education from an educational philosophy perspective. with the nature of the philosophy of education that explains the values and information sought to achieve it. This study employs the Literature Review method. The findings of this study (1) indicate that anti-corruption instruction ought to begin very early, particularly in elementary schools, because anti-corruption instruction in elementary schools aims at instilling fundamental / fundamental attitude values in students. (2) Students at the age of lower grades prioritize the cultivation of anti-corruption values regarding the small and simple things that students in the lower grades are able to achieve. Then the cultivation of anti-corruption in the high class began to be introduced to more complex anti-corruption values.